"This Is Me!" Perceptions of Older Adult Simulated Participants in an Aging and Injury Simulation Experience. Issue 1 (January 2021) - Lee, Deborah A.; Maxwell, Cathy A.; Miller, Sally
Abstract : Background: Older adults played the role of frail and prefrail geriatric trauma patients in a frailty-focused communication workshop for nurses. Although subjects played a role (acting) as simulated participants (SPs) for simulation, workshop content and role-play also applied to them personally. We aimed to explore the effect that learning frailty-focused content, scripts, and portrayal of prefrail and frail older adults has on older adult SPs. Methods: Qualitative focus group. Participants included older adults older than 70 years ( N = 6). Procedure: Focus group questions pertained to (1) the SP experience, (2) thoughts and emotions throughout the SP experience, and (3) applicability of workshop content and SP experience to personal life. The focus group lasted 90 min, was digitally recorded, and transcribed verbatim. Authors independently coded transcripts to identify categories and supporting quotations. Categories and subcategories were condensed and modified through iterative discussions. Descriptive content analysis was utilized for data analysis. Results: Six categories and 2 subcategories emerged, including (1) inevitability of aging: not playing a role (sub: inevitability of death), (2) shifting perceptions: how aging impacts thought and actions, (3) time as a factor: getting information sooner, (4) changing behavior/safety: mental recalibration, (5) attitude as a determining factor (sub: loss of independence), and (6) sharing information with others. Conclusion: The study supports the use of frailty-focused communication with older adults to prompt contemplation of aging and frailty and eventual decline/death. Providing information earlier in the aging trajectory enables time for behavior change that can prevent and delay frailty and mitigate untoward outcomes (falls, hospitalizations). Abstract : Supplemental Digital Content is Available in the Text.